SPE Eastern Regional Meeting 2003
DOI: 10.2118/84829-ms
|View full text |Cite
|
Sign up to set email alerts
|

Water Vaporization in Gas Reservoirs

Abstract: Experiments have been performed to determine the rate of water vaporization in core samples at initial water saturation. The effect of pressure on rate of water vaporization has been studied. The experiments indicate that as pressure decreases from 2000 to 1000 psi, at constant temperature of 90°C, the rate of water vaporization increases from approximately 0.016 to 0.025 g/min. The effect of increase in temperature from 90°C to 100°C, at constant pressure of 1500 psi, is to increase the rate of water vaporiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…There are only a few studies on flow-through drying available, which are relevant for CO 2 storage. Zuluaga et al investigated vaporization and salt precipitation in sand packs and sandstone for gas production wells (Zuluaga and Monsalve, 2001;. At the GHGT-10 in Amsterdam 2010, two experimental studies on dry CO 2 injection have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies on flow-through drying available, which are relevant for CO 2 storage. Zuluaga et al investigated vaporization and salt precipitation in sand packs and sandstone for gas production wells (Zuluaga and Monsalve, 2001;. At the GHGT-10 in Amsterdam 2010, two experimental studies on dry CO 2 injection have been presented.…”
Section: Introductionmentioning
confidence: 99%
“…Bacci et al (2011) reported porosity changes between 4% and 29% of the estimated initial porosity. Permeability reduction between 0% and 86% of the estimated initial permeability from sandstone core flooding experiments have also been reported (Bacci et al, 2011;Wanga et al, 2009;Zuluaga et al, 2003;Zuluaga et al, 2001).…”
Section: Introductionmentioning
confidence: 64%
“…Several researchers have confirmed that mineral precipitation could cause significant reduction in gas injectivity (Bacci et al, 2011;Place et al;Wanga et al, 2009;Zuluaga et al, 2003). Bacci et al (2011) reported porosity changes between 4% and 29% of the estimated initial porosity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…As the pressure declines at constant temperature, water is vaporised given the increase of the molar water content in the gaseous phase [4]. This process can be simulated in ECLIPSE by using the GASWAT option.…”
mentioning
confidence: 99%